Tungsten permanent chemical modifier with co-injection of Pd(NO3)(2)+Mg(NO3)(2) for direct determination of Pb in vinegar by graphite furnace atomic absorption spectrometry - Oliveira, Silvana Ruella; Oliveira, Adriana Paiva; Gomes Neto, José Anchieta [UNESP] (Elsevier B.V., 2007)
A tungsten carbide coating on the integrated platform of a transversely heated graphite atomizer (THGA((R))) used together with Pd(NO3)(2) + Mg(NO3)(2) as modifier is proposed for the direct determination of lead in vinegar by graphite furnace atomic absorption spectrometry. The optimized heating program (temperature, ramp time, hold time) of atomizer involved drying stage (110 degrees C, 5 s, 30 s; 130 degrees C, 5 s, 30 s), pyrolysis stage (1000 degrees C, 15 s, 30 s), atomization stage (1800 degrees C, 0 s, 5 s) and clean-out stage (2450 degrees C, I s, 3 s). For 10 mu L of vinegar delivered into the atomizer and calibration using working standard solutions (2.5-20.0 mu g L-1 Pb) in 0.2% (v/v) HNO3, analytical curve with good linear correlation (r = 0.9992) was established. The characteristic mass was 40 pg Pb and the lifetime of the tube was around 730 firings. The limit of detection (LOD) was 0.4 mu g L-1 and the relative standard deviations (n = 12) were typically <8% for a sample containing 25 pg L-1 Pb. Accuracy of the proposed method was checked after direct analysis of 23 vinegar samples. A paired t-test showed that results were in agreement at 95% confidence level with those obtained for acid-digested vinegar samples. The Pb levels varied from 2.8 to 32.4 pg L-1. Accuracy was also checked by means of addition/recovery tests and recovered values varied from 90% to 110%. Additionally, two certified reference materials were analyzed and results were in agreement with certified values at a 95% confidence level. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: lead; vinegar; graphite furnace atomic absorption spectrometry; tungsten carbide coating